Brainwave patterns during a mock job interview among Thai undergraduate students - Wilang, Jeffrey Dawala (Frontiers in Human Neuroscience, 2025)
This study examined the use of electroencephalography (EEG) to measure real-time cognitive engagement during English-speaking tasks among Thai undergraduate students. A total of 41 participants took part in a mock job interview while wearing a five-channel EEG headset, which captured brain activity in the beta and gamma frequency bands. The EEG data were analyzed to identify variations in neural activation associated with speaking performance. Descriptive analyses revealed that participants with higher speaking scores generally exhibited increased beta and gamma wave activity, indicating greater attentional focus and semantic processing. However, nonparametric tests showed no statistically significant differences in neural activation between the lowest- and highest-scoring groups, suggesting that cognitive engagement may not always correspond directly with observable speaking performance. These results emphasize that even lower-performing learners may exhibit strong mental effort during communication, and that EEG can serve as a valuable tool for understanding hidden cognitive processes and informing more personalized language instruction and assessment.